EFFORT MATTERS: EXPLORING INDONESIAN UNIVERSITY STUDENTS’ SELF-EFFICACY IN ENGLISH LEARNING - Sepyanda, Marsika; Fenni Kurnia Mutiya; Elviza Yeni Putri; Lucy Oktavani (Universitas Mahaputra Muhammad Yamin, 2025)
Self-efficacy plays a crucial role in shaping students' motivation and performance, particularly in the context of learning a foreign language such as English. Guided by Bandura’s (1997) social cognitive theory, this study explores Indonesian university students’ self-efficacy beliefs in English learning, with a specific focus on the role of effort-related beliefs. This study aims to explore university students' self-efficacy in English learning by analyzing their beliefs and confidence levels toward their language learning abilities. The respondents consisted of 129 students enrolled in a compulsory General English course in Universitas Negeri Padang, selected from a population of 308 students using a simple random sampling technique. A questionnaire comprising 25 items based on a Likert scale was administered to measure students’ self-efficacy. The validity and reliability of the instrument were confirmed through Pearson Product-Moment correlation and Cronbach’s Alpha (? = 0.7926), indicating strong internal consistency. Data analysis revealed that the average self-efficacy score was 3.29, which falls into the moderate category. The highest-rated statement indicated students' belief that effort leads to improvement, while the lowest-rated item reflected a sense of helplessness regardless of effort. These results suggest that while students believe in their potential to succeed in English learning through hard work, some still struggle with negative self-perceptions. The findings emphasize the importance of addressing students' self-efficacy beliefs to enhance their learning outcomes. Educational interventions that foster self-awareness, goal-setting, and motivational strategies may contribute positively to increasing self-efficacy in language learning. This study contributes to the growth of the literature on EFL self-efficacy in Indonesia. It is suggested that the lecturers to support students’ confidence and autonomy in acquiring English as a foreign language.